2017
DOI: 10.1055/s-0036-1590793
|View full text |Cite
|
Sign up to set email alerts
|

Ambident Reactivity of Nitroso Compounds for Direct Amination and Hydroxylation of Carbonyls

Abstract: Functionalization of carbonyls, particularly with a heteroatom subunit, is an important synthetic transformation. Utilization of ambident electrophiles for such a strategy is advantageous because two different heteroatom units can be installed from a single source under judicial reaction conditions. Recently, there have been increased examples for the construction of C–O and C–N bonds using nitroso compounds, a prototype of ambident electrophiles. In this short review, we discuss the advantages and challenges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Meanwhile, it is well known that hydroxyl amine is the best source of reactive nitroso (N–O bond) intermediates8 and for a decade we have used these intermediates to synthesize various new types of N-selective (C–N–O) as well as O-selective (C–O–N) bond-containing synthetically useful chiral compounds as well as bioactive compounds 9. We are eager to investigate if N–O bond formation could be achieved by choosing suitable reaction conditions using amines and benzoyl peroxide.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it is well known that hydroxyl amine is the best source of reactive nitroso (N–O bond) intermediates8 and for a decade we have used these intermediates to synthesize various new types of N-selective (C–N–O) as well as O-selective (C–O–N) bond-containing synthetically useful chiral compounds as well as bioactive compounds 9. We are eager to investigate if N–O bond formation could be achieved by choosing suitable reaction conditions using amines and benzoyl peroxide.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we previously reported the reactivity of these versatile building blocks as dienes towards aryl nitroso compounds and showed that they are valuable precursors of important heterocycles such as pyrroles, furans, nitrones and oxazines (Scheme ) . The polarization of the nitrogen–oxygen bond of nitroso derivatives confers them high reactivity . For this reason, besides [4+2] cycloadditions, they can also be involved in a large number of other processes, whether metal‐catalyzed or not, with enolizable carbonyl compounds,[4a], [4b], [4e], [4f], [4h], Grignard reagents, amines[4b], or can be used for scavenging radicals.…”
Section: Introductionmentioning
confidence: 99%
“…The polarization of the nitrogen–oxygen bond of nitroso derivatives confers them high reactivity . For this reason, besides [4+2] cycloadditions, they can also be involved in a large number of other processes, whether metal‐catalyzed or not, with enolizable carbonyl compounds,[4a], [4b], [4e], [4f], [4h], Grignard reagents, amines[4b], or can be used for scavenging radicals. [4b], [4f], Activated by an electron‐withdrawing group, they are also excellent partners for participating in ene reactions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations